Traitement Anti-inflammatoire en Pédiatrie (CHU Sétif) - HACHEMI , Yousra; DJOUDI , Aya; DEMBRI , Belkis; GHADBANE , Douaa; TCHEIR , Abderrahim (Encadrant) (Université Sétif1 Ferhat Abbas. Faculté de Médecine., 2024)
he use of anti-inflammatory drugs in pediatrics has a complex and evolving history, shaped by medical advancements, concerns about drug safety, and the specific needs of children. We conducted a retrospective and descriptive epidemiological study to evaluate the use of antiinflammatory drugs on a sample of 1200 patients hospitalized in the pediatric and neonatology departments at the CHU of Sétif (200 patients admitted to neonatology; 1000 patients admitted to pediatrics) during the period going from December 1, 2023, to April 30, 2024. We used 1200 prescriptions as well as the medical records of hospitalized patients as data collection tools. The results obtained are: • 15% of patients admitted to neonatology have an inflammatory condition ; • 21% of patients admitted to pediatrics have an inflammatory condition ; • 4% of anti-inflammatory drugs are used in neonatology : 100% corticosteroids, 0% nonsteroidal anti-inflammatory drugs (NSAIDs) ; • 22% of anti-inflammatory drugs are used in pediatrics : 100% corticosteroids, 0% NSAIDs; • Corticosteroids used in neonatology: Dexamethasone (56%), Budesonide (33%), Prednisolone (11%) • Corticosteroids used in pediatrics: Dexamethasone (16%), Budesonide (14%), HHC (4%), Prednisolone (1%). This study highlights the importance of thoughtful and careful prescription of anti-inflammatory drugs in pediatrics to ensure safe and effective care, just as it is for adults.
تمتع استخدام الأدوية المضادة للالتهاب في طب الأطفال بتاريخ معقد ومتطور، شكلته التقدمات الطبية والمخاوف المتعلقة بسلامة الأدوية والاحتياجات الخاصة للأطفال. لقد أجرينا دراسة وبائية استرجاعية ووصفية لتقييم استخدام الأدوية المضادة للالتهاب على عينة مكونة من 1200ينتمون الى قسم طب الأطفال وقسم حديثي الولادة في المستشفى الجامعي بسطيف ( 200مريض ينتمون إلى قسم حديثي الولادة؛ 1000مريض ينتمون إلى قسم طب الاطفال) خلال الفترة من 1ديسمبر 2023إلى 30أبريل .2024استخدمنا 1200وصفة طبية بالإضافة إلى سجلات المرضى كأدوات لجمع البيانات. تحصلنا على النتائج التالية: • ٪15من المرضى الذين ادخلوا إلى قسم حديثي الولادة يعانون من حالة التهاب. • ٪21من المرضى الذين ادخلوا إلى قسم طب الأطفال يعانون من حالة التهاب. • الأدوية المضادة للالتهاب المستعملة في قسم حديثي الولادة هي ٪100ستيرويدية، و ٪0غير ستيرويدية. • الأدوية المضادة للالتهاب المستعملة في قسم طب الأطفال هي ٪100ستيرويدية، و ٪0غير ستيرويدية. • الستيرويدات المستعملة في قسم حديثي الولادة هي: ديكزاميثازون ( ،) ٪56بوديزونيد ( ،) ٪33بريدنيزولون (.) ٪11 • الستيرويدات المستعملة في قسم طب الأطفال هي: ديكساميثازون ( ،) ٪16بوديزونيد ( ،) ٪14هيدروكورتيزون (،) ٪4 بريدنيزولون (.) ٪1 تسلط هذه الدراسة الضوء على أهمية الوصف الدقيق والحذر للأدوية المضادة للالتهاب في طب الأطفال لضمان رعاية آمنة وفعالة، كما هو الحال بالنسبة للبالغين
Keywords: AINS; AIS; pédiatrie; néonatologie.